Unraveling Hamlet’s Complex Relationships: A Study of Shakespeare’s Depiction of Hamlet and the Female Characters in Hamlet - Mrs. Ferdousi Akter (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research delves into the intricate relationships depicted in William Shakespeare's “Hamlet”, with a focus on Hamlet's interactions with female characters. It aims to unravel the complexities of these relationships, shedding light on Shakespeare's portrayal of gender dynamics, power struggles, and emotional entanglements. Employing a qualitative approach, the study analyzes interactions between Hamlet and characters like Ophelia and Gertrude, drawing from primary texts and scholarly analyses. Primary data sources include the original text of “Hamlet” and reputable academic commentaries, complemented by secondary sources like critical essays and historical contextualizations. Data collection involves meticulous examination of relevant play passages, supported by insights from literary criticism spanning different eras. Contemporary perspectives in gender, psychology, and cultural studies enrich understanding of character motivations. Thematic coding, textual analysis, and comparative examinations uncover patterns in Hamlet's interactions, exploring themes such as love, betrayal, and power dynamics. This research contributes to literary scholarship and broader discussions on gender and societal norms, revealing nuanced portrayals and female resilience within patriarchal constraints.